A review of CSR classification schemes and the operationalization of bolted‐on vs. built‐in CSR. Issue 3 (28th April 2021) - Rahman, Noushi; Blake, Laura
Abstract: Recent conceptualization of built‐in versus bolted‐on corporate social responsibility (CSR) initiatives has offered a much‐needed distinguishing framework to sophisticate our understanding of why different CSR initiatives yield varying corporate social performance (CSP) and associated recognition from stakeholders. One of the major roadblocks in conducting research on these two types of CSR initiatives is the absence of a valid and reliable measure. We address this void by developing a measure for bolted‐on versus built‐in CSR that relies on coding publicly available content. Our measure of these two types of CSR initiatives tests favorably for both convergent and discriminant validity and inter‐rater reliability. Advancement of such a measurement instrument will positively contribute to CSR research, enabling scholars to better theorize the linkage between CSR and reputation, and other aspects of firm performance.